Biomechanical Stress Analysis of Platform Switch Implants of Varying Diameters on Different Densities of Bone. (24th February 2022) - Mukherjee, Sandipan; Rodrigues, Shobha; M, Mahesh; Shetty, Thilak; Pai, Umesh; Saldanha, Sharon; Hedge, Puneeth; Kamath, Vignesh; Sales, Ann; Bajantri, Prashanth
Abstract : Purpose . The purpose of this study was to evaluate and compare the strain developed in D2 and D3 types of bones on vertical loading by platform switch implants of different diameters. Materials and Methods . Implants of diameters 3.25 mm, 4.2 mm, and 5.0 mm and of length 11.5 mm were taken and placed each on D2 and D3 bone models. Strain gauges were attached on the buccal and the lingual sides on each of these samples, and a vertical load of 190N was placed on the samples. The strain was recorded using a data logger. The data obtained was analysed using one-way ANOVA and post hoc Tukey test. Results . In D2 and D3 bone models, 3.25 mm significantly showed greater bone strain values. The buccal side strain was higher irrespective of the implant diameter and density of bone. Conclusion . Within the limitations of the study, it may be concluded that the narrow diameter implant produces greater strain than 4.2 and 5.0 mm diameter implants, respectively. The buccal side consistently produced higher bone strain values.